Investigation on Physical and Electrical Properties of The SiO2-ZnO Nanocomposite at different Composition Mixings - Rani, Erika; Sinol, Moh (Proceedings of the International Conference on Green Technology, 2017)
Physical and electrical properties of The SiO2-ZnO mixing at different compositions were investigated. The experiment used simple mixing method at the sintering temperature 600 o C. It was used the composition mixing ratio of SiO2:ZnO ie. 0 : 10; 7 : 3; 5 : 5; 3 : 7; and 10:0 (%Wt) . Based on X-Ray Diffraction (XRD) results, it obtained that a new phase in each sample was not formed even though having different diffraction peak. The mixing ratio of SiO 2 : ZnO nanocomposite (7:3 %wt) had the biggest grain size (77,92 nm), the highest dielectric constant (3.00E+05) and the smallest conductivity (0,726549 (Ωm) -1 ). On the other side, the mixing ratio of SiO 2 : ZnO nanocomposite (5:5 %wt) had the smallest grain size (35.42nm), dielectric constant (3.00E+2) and the highest conductivity (25.36729  (Ωm) -1 ). It can be concluded that the difference of composition ratio offered the change on both physical and electrical properties of SiO2-ZnO nanocomposite.